2022
DOI: 10.1155/2022/5125884
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Visit-to-Visit Triglyceride-Glucose Index Variability on the Risk of Cardiovascular Disease in the Elderly

Abstract: Background. e aging population is increasingly susceptible to cardiovascular disease (CVD). Visit-to-visit variability in glucose and lipid levels both contributed to CVD risk independent of their mean values. However, whether variability in the triglycerideglucose (TyG) index is a risk factor for CVD remains unknown. Research Design and Methods. In this retrospective study of electronic health records, 27,520 participants aged over 60 years were enrolled. e visit-to-visit variability of TyG index was calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The triglyceride-glucose (TyG) index, conveniently calculated by triglyceride and fasting glucose levels, has been regarded as a good alternative surrogate marker for the established parameters of IR [ 7 ]. Accumulating evidence indicated that the TyG index is associated with cardiovascular and metabolic risk, predominantly cardiovascular disease [ 8 11 ], type 2 diabetes mellitus [ 12 ], stroke [ 13 , 14 ], arterial stiffness [ 11 , 15 , 16 ], vascular damage [ 17 , 18 ] and even death [ 19 ]. Recently, a few studies reported that a higher TyG index was also associated with an increased risk of sarcopenia or low muscle mass in older populations [ 20 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The triglyceride-glucose (TyG) index, conveniently calculated by triglyceride and fasting glucose levels, has been regarded as a good alternative surrogate marker for the established parameters of IR [ 7 ]. Accumulating evidence indicated that the TyG index is associated with cardiovascular and metabolic risk, predominantly cardiovascular disease [ 8 11 ], type 2 diabetes mellitus [ 12 ], stroke [ 13 , 14 ], arterial stiffness [ 11 , 15 , 16 ], vascular damage [ 17 , 18 ] and even death [ 19 ]. Recently, a few studies reported that a higher TyG index was also associated with an increased risk of sarcopenia or low muscle mass in older populations [ 20 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was recently noted that the variability and longitudinal trajectory in the TyG-index, both regarded as novel and important indicators for outcome events, had strong predictive effects for cardiovascular diseases ( 39 42 ). With either variability or longitudinal trajectory in the TyG-index, the effects on CMDs risk in this research are consistent with a previous study that found those indicators (variability and trajectory) to be associated with CMDs risk.…”
Section: Discussionmentioning
confidence: 99%
“…Second, owing to the possibility of reverse causality, participants in the TyG level loss category were more inclined to be at high risk for having a CMDs, such as drinkers and smokers (Supplementary Table S7), who have greater odds of receiving health education about CMDs prevention and consciously lowering TyG levels. Furthermore, this phenomenon may be related to metabolic memory caused by FBG [34], considering the TyG-index calculated using the parameters FBG and TG. Notably, although we have tried to adjust for confounders adequately, there are still some force majeure factors, such as insidious disease, that may cause unintentional TyG level loss during the protracted or chronic course of the disease.…”
Section: Discussionmentioning
confidence: 99%